Electrochromic properties of pyrene conductive polymers modified by chemical polymerization. Issue 62 (9th December 2021) - Li, Rui; Xu, Haoran; Zhang, Yuhang; Chang, Lijing; Ma, Yang; Hou, Yanjun; Miao, Shoulei; Wang, Cheng
Abstract : Pyrene is composed of four benzene rings and has a unique planar melting ring structure. Abstract : Pyrene is composed of four benzene rings and has a unique planar melting ring structure. Pyrene is the smallest condensed polycyclic aromatic hydrocarbon, and its unique structural properties have been extensively studied. Pyrene has excellent properties such as thermal stability, high fluorescence quantum efficiency and high carrier mobility. This paper mainly used thiophene, EDOT and triphenylamine groups to enhance the pyrene based π-conjugated system and control the molecular accumulation of organic semiconductors, and improve their charge transport performances. Five kinds of polymer were synthesized and correspondingly characterized. The five kinds of pyrene conductive polymer had outstanding properties in terms of solubility, fluorescence intensity and thermal stability, good film-forming properties, stable electrochromic properties and high coloring efficiency. The coloration efficiency (CE) of PPYTP was as high as 277 cm 2 C −1, and the switching response time was short. The coloring time of PPYEDOT was 1.3 s and the bleaching time was 3.2 s. The lower impedance will also provide the possibility of such polymers being incorporated into electrochromic devices in the future. In short, the synthesized new pyrene conductive polymers will have wide application prospects in the field of electrochromic materials.